Prognostic value of tumor‐infiltrating lymphocytes and PD‐L1 expression in esophageal squamous cell carcinoma - Jie Hu; Takeshi Toyozumi; Kentaro Murakami; Satoshi Endo; Yasunori Matsumoto; Ryota Otsuka; Tadashi Shiraishi; Shinichiro Iida; Hiroki Morishita; Tenshi Makiyama; Yuri Nishioka; Masaya Uesato; et al. (Cancer Medicine)
Abstract Background Tumor cells (TC) participate in tumor progression by altering the immune responses in the tumor microenvironment. However, the clinical relevance and prognostic effect of PD‐L1 expression and tumor‐infiltrating lymphocytes (TILs) in esophageal squamous cell carcinoma (ESCC) are unknown. The purpose of this study was to investigate the interactions and clinical significance of PD‐L1 expression and TILs in ESCC. Methods Tissue specimens were collected from 126 patients with ESCC who underwent curative esophagectomy. Immunohistochemical analysis and multiplex immunofluorescence for CD4, CD8, CD25, FOXP3, and PD‐L1 in the tumor were used to identify multiple tumor‐infiltrating immune cells (TIIC), Tregs, and TC. Results PD‐L1 was expressed in tumor cells (PD‐L1 TC). PD‐L1 TIIC and PD‐L1 TC affected the biological behavior of TC. The positive expression rate of PD‐L1 TC and CD8+ TILs was 27.8% (35/126) and 31.7% (40/126), respectively. Kaplan–Meier analysis showed that overall survival (OS) was significantly associated with decreased CD8+ TILs and PD‐L1 TC‐positive expression, which promote ESCC progression and metastasis. Conclusion Tumor depth, CD8, and PD‐L1 TC were independent prognostic factors in ESCC, and a predictive nomogram with these three risk factors improved the accuracy of predicting OS in patients with ESCC after surgical resection. The conjoint analysis of multiple immune‐related factors is beneficial for stratifying patient survival risk.